An approach on T-S fuzzy model and control of buck-boost converter - Yuanlong Li; Zhicheng Ji (2008 7th World Congress on Intelligent Control and Automation, 2008)
Considering the nonlinearity characteristic of buck-boost converter and combining with the fine part-linear characteristic of T-S fuzzy model, a novel T-S fuzzy model of buck-boost converter is proposed in this paper. Based on the constructed model, a parametrical design method of the buck-boost converter fuzzy controller is put forward via QLF method. And the parameters of controller can be obtained by solve a group of linear matrix inequalities. Finally, a numerical example shows that the T-S fuzzy model of buck-boost converter we construct is reliable, and the fuzzy controller can get better control performance of stability and immunity to disturbance than PI control.